MG/CA Ratios in the planktonic foraminifer neogloboquadrina pachyderma (Sinistral) from LA-ICP-MS. - Bergami, Caterina; Capotondi, Lucilla; Tiepolo, Massimo; Langone, Leonardo; Giglio, Federico; Ravaioli, Mariangela (Geoitalia, 2009)
not available